The MfS Reads Rathenow - anonymous author (GDR Bulletin, 1992)
Editors' Note: We print below excerpts of a review written by an "IM" for the MfS. Review of Lutz Rathenow. einst war ich fänger im schnee. Neue Texte und Bilder aus der DDR. Berlin-West: Oberbaum, 1984. 115 p.